Respuesta :

Answer:

c. x² + 2x -5 = 0

Step-by-step explanation:

 Given expression;

         [tex]\frac{5}{x}[/tex]   = [tex]\frac{x + 2}{3}[/tex]  

Unknown:

 The quadratic equation equivalent to this expression:

Solution:

  The common denominator here is 3x;

 

    So, multiply both sides by 3x

          [tex]\frac{5}{x}[/tex] x 3x  =  [tex]\frac{x + 2}{3} x[/tex] 3x

          5 x 3 = (x + 2)x

           15 = x² + 2x

     So;

          x² + 2x - 15

The quadratic expression is x² + 2x - 15